FACTORS RELATED TO UNSAFE BEHAVIOR OF PILE WORK AT PT WASKITA KARYA (PERSERO) HIGHWAY PROJECT KLBM SECTION 2 WADUK BUNDER AREA - Dianawati, Putri; Nawawinetu, Erwin Dyah (Faculty of Vocational Studies, Universitas Airlangga, 2018)
Background: Occupational accidents are generally caused by 2 main points of unsafe action and unsafe condition. Several previous studies have shown that unsafe behavior significantly affects the onset of occupational accidents. Purpose: The purpose of this research was to study the factors associated with unsafe behavior expected to prevent the occurrence of occupational accidents. Method: This research was an observational analitical one with cross sectional design and using questionnaire to obtain primary data. The variables studied were personal factors (age, education, knowledge of Occupational, Safety and Health (OSH), fatigue and unsafe behavior. The samples of this research were 39 respondents taken randomly from population (43 workers) who were pile workers in PT Waskita Karya (Persero), Tbk KLBM Toll Project Section 2 Area Waduk Bunder. Data analysis in this research used spearman statistic test. Result: The result showed that from 39 respondents, 33 respondents (84.61%) did unsafe behavior in medium category and 6 respondents (15,39%) did unsafe behavior in high category. Of the four variables studied, researcher obtained that the value of correlation coefficient of age with unsafe behavior is -3.323, knowledge K3 with unsafe behavior is -0,545. While education and fatigue had no correlation with unsafe behavior. Conclusion: Based on the results of the study, it was concluded that the higher the age the lower the unsafe behavior or vice versa, the higher the level of knowledge of OSH the lower the unsafe behavior or vice versa.